Education regarding relationship of nutritional status to short stature and level of intelligence to parents of elementary school students - Rohmawati, Lili; Pratita, Winra; Tanjung, Ika Citra; Arto, Nindia Sugih (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Short stature is a health problem with long-term implications to the future of the children. Short stature condition in children below five years old, known as stunting, may cause cognitive, psychomotor impairment and interfere with productivity on adult period. Main concern in short stature is due to insufficient of dietary intake in long-term period. Parents’ role in the prevention of short stature is important, therefore, performing education to parents is a crucial task to the government, universities and communities to be done continuously. The objective of this educational counseling was to educate the parents so they would be able to comprehend the relationship of nutritional status to short stature, especially in children below five years old, and level of intelligence in order to prevent the condition of short stature in the future. This activity was held in conjunction with community service program Pengabdian Kepada Masyarakat Dosen Wajib Mengabdi Universitas Sumatera Utara (USU) 2019, by the lecturer team of Faculty of Medicine USU in elementary school Yayasan Pendidikan Al-Washliyah Tanjung Rejo, Medan. Educational counseling materials were modules and leaflets distributed to the parents. To evaluate the educational counseling, questionnaires were disposed prior to and after the lecture. The target audience was the parents of elementary school students, amount of 48 people. The results showed mean difference questionnaires’ score of 0.97 (SD 1.76) with 95%CI=0.46-1.49 and p value=0.001 (p<0.05). There was significant difference of parental knowledge to educational counseling material prior to and after the counseling. Concluded, parental knowledge regarding relationship of nutritional status to short stature and level of intelligence is significantly increased through the educational counseling.